IMPLEMENTASI PERATURAN DAERAH KOTA BUKITTINGGI TENTANG KETERTIBAN DAN KETENTRAMAN UMUM DALAM PENERTIBAN PEDAGANG KAKI LIMA DI KAWASAN JAM GADANG - Munawarah, Dianatul; Syafril, Rizki (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the implementation of the Regional Regulation of Bukittinggi City on Public Order and Peace in the enforcement of street vendors (PKL) in the Jam Gadang area. The research method used is qualitative with a descriptive approach. The presence of street vendors in the Jam Gadang area of Bukittinggi City has caused various problems, such as disorder, reduced pedestrian access, and disruption of the area's aesthetic appeal as a tourist destination. However, the implementation of this policy still faces challenges, particularly the non-compliance of some vendors who continue to sell in prohibited areas. The penalties imposed so far have been administrative, such as warnings and evictions, without strict sanctions that effectively deter violations. As a result, street vendors often return to selling once the authorities leave the location. This situation indicates that the effectiveness of enforcement policies needs to be improved. A more integrated strategy is required, combining law enforcement with alternative solutions for the vendors, ensuring that the policy is implemented optimally and sustainably.